Four new species and two new genera of Metapseudidae (Crustacea: Tanaidacea: Apseudomorpha) from Australian coral reefs - Stępień, Anna; Błażewicz-Paszkowycz, Magdalena (Zootaxa, 2013)
This paper presents the descriptions of two new genera and four new metapseudid species collected from the coral reefs of Ningaloo and Heron Island in north-western and eastern Australia, respectively. Two of the species, Curtipleon chadi n. sp., and Creefs heronum n. gen. n. sp. are members of the subfamily Synapseudinae, one, Msangia mussida n. sp. is a member of the subfamily Msangiinae and one Bamberus jinigudirus n. gen. n. sp. is a member of the subfamily Chondropodinae. With the exception of M. mussida that was found on live coral, all of the species were associated with dead corals.